2009
DOI: 10.1111/j.1476-5381.2009.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

NCX 2057, a novel NO‐releasing derivative of ferulic acid, suppresses inflammatory and nociceptive responses in in vitro and in vivo models

Abstract: Background and purpose:We previously reported that NCX 2057, a compound comprising a nitric oxide (NO)-releasing moiety and the natural antioxidant, ferulic acid (FA), inhibits pro-inflammatory mediators through NO-mediated gene regulation. Here, we have assessed the activities of NCX 2057 in models of inflammatory and neuropathic pain, and characterized its effects on cyclooxygenase (COX)-1 and COX-2. ]. NCX 2057 reversed carrageenan-induced hyperalgesic responses in mice and inhibited prostaglandin E2 format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Three distinctive motifs (3-methoxy and 4-hydroxy groups on the benzene ring, and the carboxylic acid group) of ferulic acid are responsible for its free radical scavenging capability. It has been also reported that ferulic acid or related ester derivatives inhibited the release of ROS and RNS via suppression of iNOS (Jiang et al, 2009) and COX-2 (Hirata et al, 2005, Ronchetti et al, 2009) in LPS-stimulated macrophages. Its reduced form, ferulaldehyde possesses the same structural characteristic and main molecular motifs as ferulic acid up to the aldehyde group.…”
Section: Reactive Oxygen and Nitrogen Speciesmentioning
confidence: 96%
“…Three distinctive motifs (3-methoxy and 4-hydroxy groups on the benzene ring, and the carboxylic acid group) of ferulic acid are responsible for its free radical scavenging capability. It has been also reported that ferulic acid or related ester derivatives inhibited the release of ROS and RNS via suppression of iNOS (Jiang et al, 2009) and COX-2 (Hirata et al, 2005, Ronchetti et al, 2009) in LPS-stimulated macrophages. Its reduced form, ferulaldehyde possesses the same structural characteristic and main molecular motifs as ferulic acid up to the aldehyde group.…”
Section: Reactive Oxygen and Nitrogen Speciesmentioning
confidence: 96%
“…Additional evidence of NO-mediated effects in neuropathic pain models was later obtained with compounds possessing both antioxidant and NO-releasing properties (Ronchetti et al, 2009). Other investigators reported the beneficial effect of NO when combined with gabapentin despite the different experimental conditions employed (Curros-Criado and Herrero, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Many studies have indicated that ferulic acid has antioxidant effects, photoprotective effects and antitumor activity, and protects against amyloid peptide toxicity [23][24][25][26][27][28][29][30][31][32][33]. In addition, it has been shown to have antihypertensive activity in spontaneously hypertensive rats.…”
Section: Introductionmentioning
confidence: 99%